Characterization and effect of extraction solvents on the yield and total phenolic content from Vernonia amygdalina leaves - Alara, Oluwaseun Ruth; Nour, A. H.; Siti Kholijah, Abdul Mudalip; Olalere, Olusegun Abayomi (Springer International Publishing, 2018)
In this study, the effects of extraction solvents on the yield and total phenolic content of Vernonia amygdalina leaf were examined. The considered solvents were water, 20% v/v ethanol, 40% v/v ethanol, 60% v/v ethanol, 80% v/v ethanol, and 100% v/v ethanol using Soxhlet extraction technique. Highest extraction yield (19.45 ± 0.22% g/g) and total phenolic content (96.25 ± 2.52 mg GAE/g d.w.) were achieved using 60% v/v aqueous ethanol solution. In addition, there exist a significant correlation between total phenolic content and antioxidant activities using DPPH (R2 = 0.9397, p < 0.05) and ABTS scavenging activity (R2 = 0.7700, p < 0.05). More so, the FTIR analysis confirmed the presence of functional groups attributed to its antioxidant property. There was a significant damage in the cell wall of V. amygdalina leaf after extracted with 60% v/v ethanol solution. Therefore, V. amygdalina leaf can be a good source of antioxidants.